Pengaruh Komposisi Media Campuran Tanah dan Biochar Sekam Padi terhadap Pertumbuhan Krisan (Chrysanthemum spp.) - Henni Elfandari; Betari Safitri (JURNAL AGROTROPIKA, 2022)
Chrysanthemum (Chrysanthemum spp.) is one of the ornamental plants that has the potential to be developed in Indonesia. In general, chrysanthemums are cultivated as cut flowers and potted flowers. The diversity of colors and shapes of chrysanthemums and the low rate of flower wilting are the main attractions of chrysanthemum plants. The demand for chrysanthemum flowers increases by 25% every year so that cultivation and production technology is needed to meet the needs of the national market. Fertilization is the addition of nutrients to plants to increase plant growth and development. One of the materials that can be given to plants is biochar. This study used one treatment in a Randomized Block Design (RAK) with four replications. The treatment of  the composition of the growing media consisted of 4 levels. Observations were made on the growth of chrysanthemum plants including plant height and number of leaves. The results showed that the planting media treatment with a composition of 50% soil + 50% biochar produced the best plant height and number of leaves compared to other treatments. This shows that the addition of biochar with the right ratio in the growing media can increase the growth of chrysanthemum plants.